ECONOMIC GROWTH: A COMPREHENSIVE ANALYSIS OF FINANCIAL AND LABOR - Wulandari , Eva; Kartikasari, Dewi; Septiani, Yustirania; Islami, Fitrah Sari (Jurnal REP (Riset Ekonomi Pembangunan), 2023)
Economic growth is an indicator that discloses the economic condition of a region. In 1990, Indonesia met its highest growth rate that had ever occurred, in which in subsequent years it tended to decline although Indonesia's financial and labor revenues increased. Therefore, this research aims to analyze the influence of financial and labor aspects on Indonesia's economic growth, both short and long-term. The research was conducted using quantitative descriptive techniques. Secondary data is in the form of time series. The analysis technique uses multiple linear regression with the ARDL (Autoregressive Distributed Lag) model. The research explains that tax revenue, and non-tax state revenue as financial indicators have a positive and significant influence, and labor has a significant negative influence in the long term, while foreign investment has a positive and insignificant influence. Tax revenues and non-tax state revenues have a positive and significant effect on Indonesia's economic growth, while foreign investment and labor have an insignificant effect in the short term for the period 1990-2022.